Analisis Implementasi Pembelajaran IPS Dalam Membentuk Karakter Nasionalisme Di Mts Miftahul Jannah Parakan Trenggalek - Guswantoro, Guntur; Rindrayani, Sulastri Rini; Sunjoto, Sunjoto (Sekolah Tinggi Agama Islam (STAIN) Curup, 2018)
The implementation of the 2013 curriculum begins with designing the design of the learning planning program in the form of syllabus and learning implementation plans which are the elaboration of core competencies and basic competencies that have been set by the National Education Standards Agency. Conceptually the development of social studies education in Indonesia is inseparable from the development of universally developing Social Studies thinking. In social studies learning mainly discusses forming the character of nationalism where the definition of ones own character is quality or mental or normal strength, morals or individual character which is a special personality that becomes a driver and driver, and that distinguishes it from other individuals. On the contrary, the explanation of nationalism means stating the superiority of a group activity based on the similarity of language, culture and region.